Analysis of Indonesian Language Error in Writing Reports of Students' Learning Results of The Amanah Fitrah Rabbani Foundation Using The Sipebi Application - Randi Ramliyana; Noor Komari Pratiwi; Yunita Endra Megiati (Universitas Indraprasta PGRI, 2022)
This study aims to describe Indonesian errors in student learning outcomes reports made by teachers at the Amanah Fitrah Rabbani Foundation in the even semester 2020/2021. This research is a qualitative research study with a descriptive approach in order to be able to describe language errors in depth. The data collection technique used in this research is the document technique. Sources of data used come from reports of student learning outcomes. The results of the student learning reports are entered into the Sipebi application developed by the Language Agency of the Ministry of Education and Culture for analysis. After that, the results of the Sipebi application were analyzed compared with the results of the analysis carried out manually in accordance with the applicable rules in the General Guidelines for Indonesian Spelling. Based on the results of the analysis and discussion of the data used, the first version of the Sipebi application still has many shortcomings that must be improved. It was because there were many kinds of language errors that it should have detected, but not detected. The types of errors that were not detected were non-standard words, bound forms, and conjunctions. For the results of the analysis of student learning outcomes written by the Amanah Fitrah Rabbani Foundation teacher, the most frequent language errors that occur are writing non-standard words, bound forms, and conjunctions.Keywords: Sipebi, application, Indonesian language error.